THE ROLE OF COLLABORATION LEVELS IN THE INFLUENCE OF TRUST LEVEL ON PROJECT MANAGEMENT SUCCESS AT DEVELOPER COMPANIES IN BATAM - Agustinus Setyawan; Annalin Annalin (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2022)
This study aims to determine and analyze the effect of the trust levels which include trust, exchange of knowledge, and expectations on project management success which includes project performance, and integration of knowledge and innovation through mediation of collaboration levels which include incentive, proximity, relationship, conflict, coordination, and commitment on developer companies in Batam. The survey conducted for this study was by distributing questionnaires to 275 respondents. The sample selection method uses purposive sampling method, which the selection of samples is in accordance with predetermined conditions that the respondents came from 5 developer companies in Batam with a total of 258 complete data to be processed. The researcher used the SPSS and Smart PLS programs to examine the effect of the independent variable on the dependent variable through the mediating variable. The results of this study indicate that the variable trust levels have a significant effect on the variable collaboration levels and project management success. However, the variable collaboration levels do not have a significant effect on the variable of project management success. Likewise, the variable of trust on variable of project management success through mediation of collaboration levels does not have a significant effect. So, it can be said that the higher the trust levels, the higher the collaboration levels and project management success will be. On the other hand, there is no influence between collaboration and project management success.